A Prospective Observational Study on Assessment of Prescribing Pattern and Effectiveness of Psychotropic Medication on Schizophrenia in a Tertiary Care Hospital - Shamnad, Muhammed; Antony, Carolin; Ajmajashy, Zainaba; K, Muktha; Huwais, Mohamed (Indian Journal of Pharmacy Practice)
Aim: Schizophrenia is a chronic mental disorder that is related to poor physical health, early death and severe functional impairment. Schizophrenia is a worldwide condition that affects 1% of the population. It refers to a category of symptoms that involve disorganized and bizarre thinking, delusions, hallucinations, inappropriate affect and poor psychosocial functioning. Aim/Background: The main aim of the study is to assess the prescribing pattern and effectiveness of psychotropic medication on schizophrenia. Materials and Methods: Patient data was collected using data collection form which included the demographic details, mental status examination, diagnosis and medications. Assessment of prescription pattern was done by analyzing the prescription of 30 patients. Effectiveness was evaluated using PANSS SCALE. Results: A total of 30 patients with schizophrenia were studied. Anti-psychotics were prescribed to 27 (90%) of the patients. Anti-depressants were prescribed to 5 (16.7%) patients. Mood stabilizers were prescribed to 2 (6.7%) patients. Tranquilizers/hypnotics were prescribed to 8 (26.7%) patients. Anti- cholinergic were prescribed to 11 (36.7%) patients. Other psychiatry drugs were prescribed to 4 (13.3%) patients. There was a significant reduction in PANSS score before and after treatment. This shows that psychotropic medication are effective in treating patients with schizophrenia. Conclusion: The present study concludes that antipsychotics are the most prescribed drugs in schizophrenia followed by anticholinergic. Psychotropic medications are effective in treating schizophrenia as it was proved by PANSS score analysis. The study report also showed that the impact of drug therapy was more effective in males than in females as it shows a significant improvement in the symptoms of schizophrenia.
Keywords: Effectiveness; Prescription pattern; Gender; Polypharmacy; PANSS and Schizophrenia